PENGARUH KECERDASAN EMOSIONAL, PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI DENGAN KEPERCAYAAN DIRI SEBAGAI VARIABEL PEMODERASI PADA PERGURUAN TINGGI SWASTA DI BATAM - Dian Efriyenti (JURNAL AKUNTANSI BARELANG, 2018)
This study is expected for accounting students to be confident that affects empathy, because students who have high confidence will be easy to empathize with others and further improve emotional intelligence in the understanding of accounting. The sign of a student understanding of accounting is not only shown from the values obtained in the course but also if the student is to follow and be able to master the concepts related, accounting science that has been acquired so far can be applied in social life or in other words in practice the world of work. Research sample at University of Riau Islands, University of Batam and International University of Batam amounted to 82 respondents. The results showed the results of emotional intelligence and learning behavior partially and simultaneously affect the level of understanding of accounting. While confidence moderate the relationship between emotional intelligence with the level of understanding of accounting, but not significant.